TMAO-Activated Hepatocyte-Derived Exosomes Are Widely Distributed in Mice with Different Patterns and Promote Vascular Inflammation - Xiang Liu; Jiazichao Tu; Ziqin Zhou; Bingxin Huang; Jianrong Zhou; Jimei Chen (Cardiology Research and Practice)
Background. Trimethylamine-N-oxide (TMAO) has been shown to be an important player in cardiovascular disease (CVD) by promoting vascular inflammation and endothelial dysfunction. We recently found that exosomes (Exos) released from TMAO-activated hepatocytes (TMAO-Exos) could significantly induce inflammation and endothelial dysfunction. However, understandings of how are the Exos secreted by hepatocytes, where are they distributed in vivo, and what effects will they have on vascular inflammation remain limited. The present study aimed to explore the hub genes involved in the production of TMAO-Exos and their distributions in vivo and effects on inflammation. Methods. The transcriptome profiles of primary rat hepatocytes stimulated with TMAO were obtained from the GSE135856 dataset in the Gene Expression Omnibus repository, and the hub genes associated with Exos were screened and verified by qPCR. Next, Exos derived from TMAO-treated hepatocytes were isolated using differential centrifugation and given intravenously to mice. After 24 h, the distributions of DiI-labelled Exos were visualized with a fluorescence microscope, and the levels of proinflammatory genes in the aorta were detected by qPCR. Results. Phgdh, Mdh2, Echs1, Rap2a, Gpd1l, and Slc3a2 were identified as hub genes that may be involved in the production of TMAO-Exos. And TMAO-Exos were found to be efficiently taken up by cardiomyocytes, hepatocytes, and endothelial cells in the aorta and gastrocnemius muscle. Furthermore, TMAO-Exos, but not control-Exos, could significantly promote the mRNA expressions of Tnf, Icam1, Sele, and Cox-2 in the aorta. Conclusions. We provided clues about how TMAO may stimulate hepatocytes to produce Exos and further offered evidence that Exos secreted by TMAO-treated hepatocytes could be widely distributed in vivo and promote vascular inflammation.